(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article is devoted to the improvement and reconstruction of folk instruments. A topic raised on the basis of scientific and practical research by V. Belyaev, F. Karomatov, F. Sadykov, G. Kuznetsova, A. Dadamukhamedov and A. Gochbakarov. The historical and modern improvement of folk instruments used in performing practice is gradually studied and comparatively analyzed. In particular, the promotion of the rubob-prima instrument by modern musicians and their results were also briefly discussed.